The Role of The State in Promoting the Competitiveness of Cooperative Enterprises in Indonesia in Accordance with The Mandate of the 1945 Constitution: English - Hamdan Azhar Siregar; Ahmad Munawir Siregar; Mipasya Ratu Plamesti; Dhea Nur Afriana (AMCA, 2026)
The role of the state/government is particularly important in determining various economic policies, especially those closely related to efforts to develop cooperatives. Economic policies issued by the government, whether directly or indirectly, should have an impact on the development of cooperatives. The issue addressed in this paper is how the state can enhance the competitiveness of cooperatives among other business entities. What challenges does the government face in enabling cooperatives to compete with other business entities. This study uses normative legal research with a descriptive analytical nature, while the data collection technique is through literature study or document study. However, field data is also used to support and supplement library data. After the data is collected, it is analyzed using qualitative legal methods. In relation to the role of the state/government in empowering cooperatives, the evaluation of cooperative performance shows that, so far, excessive support or involvement from the government has not been able to improve the independence and performance of cooperatives. In this case, it has actually created a strong dependence of cooperatives on government programs. To avoid dependence on the government, it is now time for cooperatives to have clear and transparent regulations, and if necessary, to redefine the government's role in the empowerment and development of cooperatives, with a clear statement that cooperatives are essentially autonomous institutions. The results of this evaluation are then used as a guide in determining the boundaries or regulatory framework regarding the government's role itself, ultimately leading to an ideal pattern of relationships or interactions that benefit the development of cooperatives